Optimalisasi Pendidikan Islam melalui Pembelajaran Berbasis Cara Kerja Otak - Eni Purwati (Islamica: Jurnal Studi Keislaman, 2016)
This article is concerned with the idea of optimali-zation of Islamic education through brain perform-ance-based learning. As one of the complex part of human body, brain always develops and is able to learn of its-self. The learning process which is appropriate with the work of brain is intended to attract students in order to promote their awareness and have their knowledge stored solidly in their memory. Therefore, the learning process should consider the works and functions of each component of brain: first, reptile serves to regulate the heart and breath; second, lymbic system serves to regulate the system of body immunity, hormon, family need, social stratification, sense of belonging and the realm of emotion; third, neo-cortex serves to regulate the logic, respond something with reason, and control the world of creativity. Teachers should direct students to their human existence that they are the creature of God. This means that what is taught and learnt should be dedicated for individual and social life as a means of worship and service to God.